Efektivitas Mengunyah Permen Xyilitol Dapat Mengurangi Indeks Plak Siswa Kelas IV - Utari Zulkaidah; Arsad Arsad; Nurna Mitra Putri; Rezki Dirman; Yulistina Yulistina (Journal of Pharmaceutical and Health Research, 2023)
Teeth and mouth are part of the early stages of the digestive process. Teeth are located in the oral cavity which have several functions.Dental and oral health requires attention and is kept clean, including mechanical and chemical control so that it can carry out its functions properly.Poor dental cleaning can lead to plaque buildup and lead to tooth decay or gingivitis.Plaque is a bacterial biofilm structure that is well placed and adheres to the tooth surface. Plaque control measures can be achieved by using anti-plaque chemicals, namely xyilitol candy.Xylitol gum can reduce Streptococcus mutans because bacteria cannot metabolize xylitol into energy.The purpose of this study was to determine the plaque index before and after chewing gum containing xylitol and the relationship between before and after chewing xylitol gum. This type of research is experimental with a pre-post test design with total sampling.The results of this research from 25 respondents obtained before chewing xylitol gum there were 2 respondents who had good plaque criteria, after chewing xylitol gum there were 23 respondents who had good plaque criteria, the mean value was obtained 15.00 to 8.36, which means there is a decrease in score plaque index with a p-value of 0.004 there is a significant difference between before and after chewing xylitol gum.The conclusion of this study is that there is a decrease in the Denris index score after chewing xylitol gum and there is a significant difference between before and after chewing xylitol gum.